A GREEN URBAN FUTURE : Scaled-Up Perspectives in Urban Green for Human-Centered and Livable Urban Cores - Jones, Ana Maria; Wilenius, Markku (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
This report has been prepared in the frame of the Green-In-TURKU Project; Towards a Greener Urban Future: Investigating Innovative Solutions to Increase Livability in the Inner City-Perspectives for the City of Turku to provide Turku’s city officials with a state-of-the-art update on global greening strategies across European cities and abroad. The report introduces fresh perspectives for how cities are promoting the value in green capital to find solutions to local challenges and it is the first of three reports scheduled for this project. A second report A Study of Green And Open Spaces in Turku has been prepared as part of an in-depth investigation of Turku’s urban structure including past and present developments in the green front, and it will be integrated into the project’s final report and spatial analysis with recommendations for increasing urban vibrancy and livability in the city center of Turku.